1991
DOI: 10.1364/josaa.8.001657
|View full text |Cite
|
Sign up to set email alerts
|

Slow and fast pathways in the human rod visual system: electrophysiology and psychophysics

Abstract: Under most conditions, increasing the intensity of a flickering light makes the flicker more conspicuous. For a light flickering at 15 times per second, however, increasing the intensity can cause the flicker to disappear before reappearing again at higher intensities [Vision Res. 29, 1539 (1989)]. This flicker disappearance or null is also evident in human electrophysiological recordings at the same intensity levels. These results point to a duality within the rod visual pathway, in which flicker signals trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
58
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 39 publications
15
58
0
Order By: Relevance
“…At higher flash strengths, the perception of flicker reappears and becomes more pronounced [8][9][10][11][12]. In later studies, this disappearance of flicker perception was found to correlate with a minimum in the amplitude versus flash strength curve of 15 Hz flicker electroretinograms (ERGs) [13,14]. The minimum is accompanied by a phase shift of approximately 180°.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At higher flash strengths, the perception of flicker reappears and becomes more pronounced [8][9][10][11][12]. In later studies, this disappearance of flicker perception was found to correlate with a minimum in the amplitude versus flash strength curve of 15 Hz flicker electroretinograms (ERGs) [13,14]. The minimum is accompanied by a phase shift of approximately 180°.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, the phenomenon could also be recorded in subjects with complete achromatopsia (patients with no cone function) [13,21]. However, there are also indications in the literature, which imply that cone pathway contributions (cone signals that travel either via ON cone bipolar cells to ON ganglion cells or via OFF cone bipolar to OFF ganglion cells) are present in the responses just above the minimum [8,10,13]. Moreover, the stimuli normally applied in ERG studies do not suppress cone activity.…”
Section: Introductionmentioning
confidence: 99%
“…The squares in both panels represent the lowest amplitude at which flicker can just be seen measured as a function of intensity; the upright and inverted triangles (in the 14 Hz data only), the lower and upper limits, respectively, of the null region within which suprathreshold flicker is no longer seen. At 14 Hz, a null is found because the signals from 7~~ and X; are approximately out of phase Stockman et al, 1991). At 8 Hz, no null is present because the signals are only approx.…”
Section: Flicker Threshold Us Intensity Curvesmentioning
confidence: 95%
“…Psychophysical data (Conner & MacLeod, 1977;Conner, 1982;Sharpe, Stockman & MacLeod, 1989) and electroretinographic (ERG) recordings (Stockman, Sharpe, Zrenner & Nordby, 1991) in the normal and achromat observer demonstrate that rod flicker signals have access to both a slow and a fast retinal pathway. The slower pathway [labeled a,, after the notation of Stiles (1978)] is more sensitive and dominates from absolute threshold up to low mesopic levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation